Analytical Investigation of Precast Post-Tensioned Column of Ultra-High Performance Concrete (UHPC) - Mohammed Saeed Dahi, Saleh (IRC, 2016)
Ultra-high performance concrete (UHPC) is a new technology and development in concrete industry. UHPC has the strength more than 150 N/mm2 and it has improved properties compared to normal strength concrete (NSC). There were many tests have been conducted in order to examine and finalize the properties and the components of UHPC. Compressive strength and tensile strength for ultra-high performance concrete are the most and popular properties that have been tested. Unlike UHPC with steel fibers, NSC is brittle and it has low tensile and compressive strength. Also it has low ability to resist more loads especially lateral loading such as earthquake. Therefore, this research is aimed to develop a three dimensional (3D) nonlinear finite element model for precast pretension column of UHPC and NSC with UHPC jacketing. The model of precast pretention column is developed by using ANSYS software version 15.0 and it has been verified and validated with experimental work carried out on this column. The model of column consists of UHPC and NSC with UHPC jacketing is simulated and analyze using finite element method in order to study the influence of ultra-high performance concrete that subjected to different parameters such as compressive and tensile strength for the column under both axial and lateral loading. The result showed the influence of different compressive and tensile strength of UHPC and UHPC jacketing where this influence is parametrically investigated in terms of ultimate load and displacement the column can carry as well as the amount of cracks and average induced.